Framework for project-based learning (PJBL) in providing real world experience for electrical engineering students - Noordin, M. K. (Serials Publications, 2017)
Universities nowadays keep receiving complaints from the industry regarding the capability of engineering graduates to work. This problem is actually caused by the lack of exposure to the world of work given to the engineering students by the university. Therefore, it is imperative to give and expose the engineering students towards real world experience. Project-Based Learning (PjBL) is a teaching method that is appropriate to be implemented on engineering students. Hence, this research was conducted to investigate the effectiveness PjBL in providing real-world experience to electrical engineering students based on the opinions and perceptions of students and lecturers. This study also intended to develop a framework of PjBL that can be used to as an effective teaching method in order to provide real world experience to the electrical engineering students. This study used a qualitative method in which the data were collected by using interviews and observations. The respondents for this study were the students and lecturers that were involved in the PjBL from two universities in Malaysia. The results of this study found that the students and lecturers agreed that PjBL is an appropriate teaching method to provide real-world experience to students, where the students were exposed to the actual practices of an engineer in the industry and also able to learn the skills needed by engineer. Therefore, this study suggests that the proposed PjBL framework can be used to teach the engineering students in order to expose them with real world experience.